2012
DOI: 10.1007/s11325-012-0791-2
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor activity in patients with obstructive sleep apnea

Abstract: OSA is associated with enhanced expression and signaling events downstream of TLR2 and TLR4 in circulating monocytes. These observations are mitigated by CPAP therapy, which suggest that TLR2 and TLR4 activation may be involved as a signaling mechanism in immune-mediated progression of atherosclerosis in OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…In the present study, we found that both TLR2/6 co-expression and TLR2 expression on monocyte were increased either in SDB patients with low Min SaO 2 or with IHR treatment in vitro. In accordance with our results, enhanced expression and downstream signaling events of TLR2 and TLR4 were demonstrated in circulating monocytes from OSA patients and reversed with CPAP treatment in a recent study [31]. High TLR2 expression level on monocytes has been reported to be an independent risk factor associated with atherogenesis [32].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found that both TLR2/6 co-expression and TLR2 expression on monocyte were increased either in SDB patients with low Min SaO 2 or with IHR treatment in vitro. In accordance with our results, enhanced expression and downstream signaling events of TLR2 and TLR4 were demonstrated in circulating monocytes from OSA patients and reversed with CPAP treatment in a recent study [31]. High TLR2 expression level on monocytes has been reported to be an independent risk factor associated with atherogenesis [32].…”
Section: Discussionsupporting
confidence: 92%
“…Monocytes isolated from OSA patients have elevated TLR2 and TLR4 expression (Akinnusi et al . ), suggesting increased pro‐inflammatory responses in these cells. In agreement, TLR2, TLR4 and pro‐inflammatory cytokine expression in OSA patients are normalized by Continuous Positive Airway Pressure (CPAP), suggesting a causal role for CIH and/or sleep fractionation (Akinnusi et al .…”
Section: Introductionmentioning
confidence: 98%
“…Toll-like receptor 4 (TLR4), a typical representative of pattern recognition receptors in innate immune responses, plays an important role in activation of inflammation in atherosclerosis. It has been recently demonstrated that IHR accelerated growth and vulnerability of atherosclerotic plaque, which probably acted by triggering the activation of TLR4/NF-κB signaling [4][5][6][7]. Acting as both up-stream and down-stream mediators of TLR signaling, tumor necrosis factor (TNF)-α has been shown to be upregulated in OSA patients, and this increase became more pronounced with the more severe grades of OSAS, indicating that TNF-α might be a promising circulating biomarker for the development of OSA [8].…”
Section: Introductionmentioning
confidence: 99%